2011
DOI: 10.1074/jbc.m110.151043
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric Rhodopsin Is Sufficient for Normal Rhodopsin Kinase (GRK1) Phosphorylation and Arrestin-1 Binding

Abstract: G-protein-coupled receptor (GPCR) oligomerization has been observed in a wide variety of experimental contexts, but the functional significance of this phenomenon at different stages of the life cycle of class A GPCRs remains to be elucidated. Rhodopsin (Rh), a prototypical class A GPCR of visual transduction, is also capable of forming dimers and higher order oligomers. The recent demonstration that Rh monomer is sufficient to activate its cognate G protein, transducin, prompted us to test whether the same mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
182
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(199 citation statements)
references
References 81 publications
17
182
0
Order By: Relevance
“…Site-directed spin-labeling studies, on the other hand, revealed a high flexibility of this arrestin region upon binding to both highly activated P-ROS* and nanodiscs containing only monomeric P-rhodopsin* (28). In absence of a second receptor, the mostly hydrophobic C edge could thus interface with the phospholipid membrane in agreement with the strong lipid dependence of arrestin-rhodopsin complex formation (19,33,43). Lys232 and Gln195 close to the C edge may interact with acidic phospholipids known to facilitate rhodopsin binding (43).…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…Site-directed spin-labeling studies, on the other hand, revealed a high flexibility of this arrestin region upon binding to both highly activated P-ROS* and nanodiscs containing only monomeric P-rhodopsin* (28). In absence of a second receptor, the mostly hydrophobic C edge could thus interface with the phospholipid membrane in agreement with the strong lipid dependence of arrestin-rhodopsin complex formation (19,33,43). Lys232 and Gln195 close to the C edge may interact with acidic phospholipids known to facilitate rhodopsin binding (43).…”
Section: Resultsmentioning
confidence: 51%
“…In the visual system, arrestin-1 saturates phosphorylated light-activated rhodopsin at a 1:1 molar ratio (32) and binds monomeric rhodopsin reconstituted into nanodiscs with high affinity (19,33). Our mutagenesis data show that both arrestin grooves do not bind rhodopsin to the same extent ( Fig.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…However, it has been reported that arrestin-1 saturates rhodopsin at a 1:1 molar ratio (39) and binds the P-Rh* monomer in nanodiscs with physiological affinity and stoichiometry (40,41), supporting a one-to-one binding model. In contrast, two recent studies showed that the apparent binding stoichiometry depends on the percentage of active receptors in native disk membranes, and that arrestin-1 binding at high levels of activated rhodopsin is bestdescribed by a combination of 1:1 and 1:2 interactions (42, 43).…”
mentioning
confidence: 99%
“…About a decade ago, evidence began to emerge that rhodopsin may exist as a dimer, based on atomic force microscopy and cross-linking experiments performed on rod outersegment (ROS) disk membranes (7-9). However, this concept remains highly controversial because of the lack of in vivo evidence and also is puzzling because, unlike many GPCRs, monomeric rhodopsin is fully functional with respect to coupling to G protein (2, 4-6, 10) and to interactions with rhodopsin kinase and arrestin (11,12). In vivo evidence, albeit of paramount importance, is also challenging, because rhodopsin always exists as a single isoform in rod photoreceptors, thus making homomeric, higher-order complexes difficult to distinguish from monomers.…”
mentioning
confidence: 99%